Medical problems in children with Down syndrome - Vadakedom, Suresh S.; Krishnan, Deepa K.; Mammen, Darly Saramma; P., Bindhu K.; Antony, Jiji Mary (International Journal of Advances in Medicine, 2018)
Background: Down syndrome (DS) is a major cause of mental retardation of prenatal origin and has several associated co-morbidities involving cardiovascular system, respiratory, endocrine system, hematological, gastrointestinal, musculoskeletal, eye and ear defects, immunological changes and neurological system. This study was conducted to identify the common medical problems in children with Down syndrome and the morbidity associated with these conditions. The objective of the present study was to find out the occurrence of different medical problems in children with DS. Methods: 42 children with a phenotype of Down syndrome in the age group of 0-12 years attending the outpatient, inpatient and Down syndrome Clinic of the Institute of Child Health, Kottayam during the study period were included in the study by purposive sampling. Demographic details were entered, and Pediatric Clinical Examination was performed by the investigator himself to identify the medical problems. Old medical reports were reviewed, and data entered into a proforma and statistically analysed. Results: Out of the 42 children with DS, 22 were males. 15 (35.7%) were less than 1 year, 20 (48.3%) children 1-5 years and 7 (16.1%) children 5-12 years of age. Mean age of the study group was 1.78±0.51 years. Mean age of their mothers at the time of conception was 30.6±5.8 years. 26 (57%) children with Down syndrome had a medical problem during the neonatal period which required hospitalization. Almost all systems are affected and craniofacial features, developmental delay and hypotonia were universal. Various forms of congenital heart diseases were observed in 67% and hypothyroidism in 23.8%. Conclusions: Down syndrome is a common genetic disorder with multisystem involvement. Congenital heart diseases, hypothyroidism and recurrent respiratory infections were the common medical problems identified in this study.